2007
DOI: 10.1021/jo070847e
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of 5-Alkylsalicylates, 5-Alkyl-2-hydroxy-acetophenones, and 5-Alkyl-2-hydroxy-benzophenones by [3 + 3] Cyclization of 1,3-Bis(silyl enol ethers) with 2-Alkyl-1,1,3,3-tetraethoxypropanes

Abstract: A variety of 5-alkylsalicylates, 5-alkyl-2-hydroxy-acetophenones, and 5-alkyl-2-hydroxy-benzophenones was regioselectively prepared by TiCl4 mediated formal [3 + 3] cyclization of 1,3-bis(silyl enol ethers) with 2-alkyl-1,1,3,3-tetraethoxypropanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The structure of 13a was independently confirmed by X-ray crystal structure analysis (Figure 4). [32] Chan et al were the first to report TiCl 4 -mediated cyclizations between 1,3-bis(silyloxy)buta-1,3-dienes and 1,1,3,3-tetramethoxypropane (14a), [26] whereas we have reported [35] TiCl 4 -mediated cyclizations between 1,3-bis(silyloxy)buta-1,3-dienes and the 1,1,3,3-tetraethoxypropanes 14b-e, which are available in three steps by a known protocol. [36] TiCl 4 -mediated cyclizations between the chlorinated diene 3a and 14a-e afforded the 3-chlorosalicylates 15a-e (Scheme 10, Table 6).…”
Section: Resultsmentioning
confidence: 82%
“…The structure of 13a was independently confirmed by X-ray crystal structure analysis (Figure 4). [32] Chan et al were the first to report TiCl 4 -mediated cyclizations between 1,3-bis(silyloxy)buta-1,3-dienes and 1,1,3,3-tetramethoxypropane (14a), [26] whereas we have reported [35] TiCl 4 -mediated cyclizations between 1,3-bis(silyloxy)buta-1,3-dienes and the 1,1,3,3-tetraethoxypropanes 14b-e, which are available in three steps by a known protocol. [36] TiCl 4 -mediated cyclizations between the chlorinated diene 3a and 14a-e afforded the 3-chlorosalicylates 15a-e (Scheme 10, Table 6).…”
Section: Resultsmentioning
confidence: 82%
“…(2-Hydroxy-5-methylphenyl)(phenyl)methanone (2a). 28 The representative general procedure mentioned above was followed. Purification by PTLC on silica gel (petroleum ether/ethyl acetate = 200/1) yielded the title compound 2a in 99% (42.0 mg) as a yellow solid; mp, 70−73 °C; reported mp, 81 °C; R f = 0.35 (petroleum ether/ ethyl acetate = 200/1).…”
Section: -Methyl-3-(4′-(trifluoromethyl)-[11′-biphenyl]-4-yl)benzofur...mentioning
confidence: 99%
“…The TiCl 4 -mediated cyclocondensation of 1,3-bis(silyloxy)-1,3-butadienes with 1,1,3,3tetramethoxypropane and 2-alkyl-1,1,3,3-tetraethoxypropanes has also been reported. 12,13 Recently, we have developed a catalytic variant of this reaction using trimethylsilyl trifluoromethanesulfonate (TMSOTf) as the catalyst. 14 Chan et al reported the synthesis of 2-(phenylthio)benzoates by TiCl 4 -mediated [3+3] cyclization of 3-(silyloxy)-2-en-1-ones with 3-(arylthio)-1-(trimethylsilyloxy)-1,3-butadienes.…”
mentioning
confidence: 99%